Respostas
respondido por:
1
( 5m³ + 4 )² =
(5m³)² + 2 . 5m³ . 4 + 4² =
25m⁶+ 40m³ + 16
b
( 3x⁴ - 4y² )² =
( 3x⁴)² - 2. 3x⁴ . 4y² + ( 4y²)² =
9x⁸ - 24x⁴y² + 16y⁴
c
( 3y⁵ + 7 )² =
( 3y⁵)² + 2. 3y⁵. 7 + 7² ) =
9y¹⁰ + 42y⁵ + 49
(5m³)² + 2 . 5m³ . 4 + 4² =
25m⁶+ 40m³ + 16
b
( 3x⁴ - 4y² )² =
( 3x⁴)² - 2. 3x⁴ . 4y² + ( 4y²)² =
9x⁸ - 24x⁴y² + 16y⁴
c
( 3y⁵ + 7 )² =
( 3y⁵)² + 2. 3y⁵. 7 + 7² ) =
9y¹⁰ + 42y⁵ + 49
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás